A phase IIb multicentre study comparing the efficacy of trabectedin to doxorubicin in patients with advanced or metastatic untreated soft tissue sarcoma: The TRUSTS trial. Issue 10 (July 2015) - Bui-Nguyen, B.; Butrynski, J.E.; Penel, N.; Blay, J.Y.; Isambert, N.; Milhem, M.; Kerst, J.M.; Reyners, A.K.L; Litière, S.; Marréaud, S.; Collin, F.; van der Graaf, W.T.A; et al.
Abstract Purpose To evaluate whether trabectedin as first-line chemotherapy for advanced/metastatic soft tissue sarcoma prolongs progression-free survival (PFS), compared to doxorubicin and, in the phase IIb part here, to select the most appropriate trabectedin treatment schedule (3-hour or 24-hour infusion) in terms of safety, convenience and efficacy. Patients and methods In this randomised multicentre prospective dose-selection phase IIb superiority trial, 133 patients were randomised between doxorubicin (n = 43), trabectedin (3-hour infusion, T3h) (n = 47) and trabectedin (24-hour infusion, T24h) (n = 43). PFS was defined as time from random assignment until objective progression by response evaluation criteria in solid tumours (RECIST 1.1), a global deterioration of the health status requiring discontinuation of the treatment, or death from any cause. Results The study was terminated due to lack of superiority in both trabectedin treatment arms as compared to the doxorubicin control arm. Median PFS was 2.8 months in the T3h arm, 3.1 months in the T24h arm and 5.5 months in the doxorubicin arm. No significant improvements in PFS were observed in the trabectedin arms as compared to the doxorubicin arm (T24h versus doxorubicin: hazard ratio (HR) 1.13, 95% confidence interval (CI) 0.67–1.90, P = .675; T3h versus doxorubicin: HR 1.50, 95% CI 0.91–2.48, P = .944). Only one toxic death occurred in the T3h arm, but treatment had to be stopped due to toxicity in 7 (15.2%) (T3h), 8 (19.5%) (T24h) and 1 (2.5%) doxorubicin patients. Conclusion Doxorubicin continues to be the standard treatment in eligible patients with advanced/metastatic soft-tissue sarcoma (STS). Trabectedin 1.5 mg/m2/24-hour infusion is the overall proven approach to delivering this agent in the second-line setting for patients with advanced or metastatic STS.